Morphological study of the newly designed cementless femoral stem - Baharuddin, Mohd Yusof; Salleh, Sh-Hussain; Zulkifly, Ahmad Hafiz; Lee, Muhammad Hisyam; Mohd Noor, Alias (Hindawi Publishing Corporation, 2014)
A morphology study was essential to the development of the cementless femoral stem because accurate dimensions for both the periosteal and endosteal canal ensure primary fixation stability for the stem, bone interface, and prevent stress shielding at the calcar region. This paper focused on a three-dimensional femoral model for Asian patients that applied preoperative planning and femoral stemdesign. We measured various femoral parameters such as the femoral head offset, collodiaphyseal angle, bowing angle, anteversion, and medullary canal diameters from the osteotomy level to 150mm below the osteotomy level to determine the position of the isthmus.Other indices and ratios for the endosteal canal, metaphyseal, and flares were computed and examined.The results showed thatAsian femurs are smaller thanWestern femurs, except in the metaphyseal region.Thecanal flare index (CFI)was poorly correlated (r >0.50) to the metaphyseal canal flare index (MCFI), but correlated well (r >0.66) with the corticomedullary index (CMI). The diversity of the femoral size, particularly in the metaphyseal region, allows for proper femoral stem design for Asian patients, improves osseointegration, and prolongs the life of the implant.